56. Vaterlädischer Abend. (Danzig : [s.n.], 1925)
Druk z programem wieczoru artystycznego, który miał miejsce w Auli Conradinum 26 list. 1925 r.
Keywords: Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- źródła